Human Security: a paradigm contradicting the national interest? - Schutte, Robert; Fordelone, Talita Yamashiro (Carta Internacional, 2006)
Human Security has sparked remarkable turmoil throughout the epistemic community of international relations during the last years1. Being on the one hand popularized by international organizations like the United Nations2, on the other hand proclaimed as a practical foreign policy posture by states like Japan, Norway and Canada, this apparently innovative concept of security imposes itself to the scientific discussion. Human security refers to the human being and its individual security as a pattern of international relations, widening thereby the scientific perspective to threats beyond military security taking into account interrelated problems of under-development and human rights3. This orientation represents in fact a crucial contestation to the current hegemonic paradigms of realism and neo-realism with their concentration on interstate security competition. However, there is not only dispute about questions of analysis and explication, but also divergence concerning the normative character of this new paradigm. Human Security claims to deliver an analytical framework for research and explanation of security problems, but moreover, as a normative concept, it also demands to be a practical signpost fully applicable to foreign policy. Such a political predisposition renders the emerging paradigm of Human Security especially sensitive to reproaches put forward by competing schools of thought in international relations theory: Is the concept nothing but idealistic hot air4, inapt to confront the rough reality of an anarchic international system which forces all states to care but for their own national interest? Doubting the applicability of the Human Security paradigm to real politics means neglecting an essential component and motif of Human Security as a whole, committing thereby a deadly blow to its legitimacy. Putting it simply: Who needs a signpost signing nothing but abstract theory?